Biblical hermeneutics a treatise on the interpretation of the Old and New Testaments - Terry, Milton Spenser, 1840-1914 (Grand Rapids, MI Zondervan, 1974)
Includes bibliograhical references and index.
Keywords: Hermeneutics; Bible -- criticism, interpretation, etc